2017
DOI: 10.14814/phy2.13101
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of substrate oxidation during prolonged exercise in men at terrestrial altitude and normobaric normoxia following the coingestion of13C glucose and13C fructose

Abstract: This study compared the effects of coingesting glucose and fructose on exogenous and endogenous substrate oxidation during prolonged exercise at altitude and sea level, in men. Seven male British military personnel completed two bouts of cycling at the same relative workload (55% W max) for 120 min on acute exposure to altitude (3375 m) and at sea level (~113 m). In each trial, participants ingested 1.2 g·min−1 of glucose (enriched with 13C glucose) and 0.6 g·min−1 of fructose (enriched with 13C fructose) dire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
30
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(40 citation statements)
references
References 49 publications
(133 reference statements)
7
30
3
Order By: Relevance
“…Our data challenge common recommendations to increase the carbohydrate intake during exercise at high altitude (>2,500 m) to fuel exercise metabolism and augment endurance capability (Koehle, Cheng, & Sporer, 2014). As such, we read with interest the recent report by Sumi et al (Sumi, Hayashi, Yatsutani, & Goto, 2020), as their findings, on the surface, appear to confirm our previous results (Margolis et al, 2019;O'Hara et al, 2017O'Hara et al, , 2019Young et al, 2018). Their randomized crossover study aimed to investigate the effects of acute hypoxia on exogenous glucose oxidation in nine unacclimatized lowlanders performing 30-min of absolute or relative intensity-matched aerobic exercise.…”
Section: Isotope Tracer Assessment Of Exogenous Glucose Oxidation Dursupporting
confidence: 77%
See 2 more Smart Citations
“…Our data challenge common recommendations to increase the carbohydrate intake during exercise at high altitude (>2,500 m) to fuel exercise metabolism and augment endurance capability (Koehle, Cheng, & Sporer, 2014). As such, we read with interest the recent report by Sumi et al (Sumi, Hayashi, Yatsutani, & Goto, 2020), as their findings, on the surface, appear to confirm our previous results (Margolis et al, 2019;O'Hara et al, 2017O'Hara et al, , 2019Young et al, 2018). Their randomized crossover study aimed to investigate the effects of acute hypoxia on exogenous glucose oxidation in nine unacclimatized lowlanders performing 30-min of absolute or relative intensity-matched aerobic exercise.…”
Section: Isotope Tracer Assessment Of Exogenous Glucose Oxidation Dursupporting
confidence: 77%
“…In conclusion, while it appeared that results from Sumi et al (2020) confirmed previously published findings from our laboratories (Margolis et al, 2019;O'Hara et al, 2017O'Hara et al, , 2019Young et al, 2018), careful examination of their methodological approach revealed several limitations that preclude drawing any conclusions regarding the effects of acute hypoxia exposure on exogenous glucose oxidation during aerobic exercise. However, it is clear that exogenous glucose oxidation is lower in unacclimatized lowlanders performing aerobic exercise matched for relative (O'Hara et al, 2017(O'Hara et al, , 2019 or absolute (Margolis et al, 2019;Young et al, 2018) intensities under acute hypoxic conditions compared to normoxia. We are certainly encouraged to see other laboratories reassessing metabolic fueling strategies for exercise at high altitude, as the complex mechanisms contributing to these differences are likely multifactorial, resulting from lower exogenous glucose absorption/release from the gut and impaired peripheral insulin sensitivity and resultant glucose uptake (Margolis et al, 2019).…”
Section: Isotope Tracer Assessment Of Exogenous Glucose Oxidation Dursupporting
confidence: 71%
See 1 more Smart Citation
“…Ingesting carbohydrate during endurance exercise at sea level (SL) increases exogenous carbohydrate oxidation and limits endogenous carbohydrate utilization ( Jeukendrup et al, 1997 ; Jeukendrup, 2004 , 2008 ). Only two studies have investigated how hypoxia affects oxidation of exogenous carbohydrate ingested during exercise, and the observations reported from those studies differ ( Peronnet et al, 2006 ; O’Hara et al, 2017 ). When carbohydrate was ingested during exercise at 77% O 2max in normoxia and hypoxia equivalent to 4,300 m, exogenous carbohydrate oxidation was the same ( Peronnet et al, 2006 ).…”
Section: Introductionmentioning
confidence: 99%
“…It has previously been postulated that hypoxaemia may enhance utilization of glucose by mechanisms that are yet to be fully elucidated (17)(18)(19) and reduce reliance on fat as a substrate (20). However, we have recently shown that acute exposure to HA reduces carbohydrate oxidation and increases fat oxidation during walking (21) and prolonged cycling exercise (22). These contrasting results may be due to differences in energy consumption because the degree to which blood glucose increases on rapid ascent to 4300m is higher if energy intake is adequate (23).…”
Section: Introductionmentioning
confidence: 96%